2019
DOI: 10.1088/1361-6463/ab373a
|View full text |Cite
|
Sign up to set email alerts
|

Influence of N2, O2, and H2 admixtures on the electron power balance and neutral gas heating in microwave Ar plasmas at atmospheric pressure

Abstract: A combination of optical emission and absorption spectroscopy of argon 2p –1s transitions (Paschen notation) combined with collisional-radiative (CR) modelling of argon 2p  states was used to characterize microwave argon plasmas at atmospheric pressure in presence of N2, O2, and H2 admixtures. In particular, the neutral gas temperature (obtained from the broadening of argon 2p 2–1s2 and 2p 3–1s2 emission lines), the number density of argon 1s5 atoms (obtained from absorption spectroscopy of the argon 2p 9–1s5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 60 publications
4
16
1
Order By: Relevance
“…Figure 10c shows that, regardless of water conductivity, continuously increases from ~2700 K to ~3400 K as N2 content increases from 0 to 2.5%. Previous studies have shown that such increase in temperature is due to the excitation of N2 rotational levels, with contributions from other phenomena such as excitation of vibrational and electronic levels, ionization, and dissociation [25], [28], [29]. Although this explanation is very well accepted for gas-phase microwave plasmas, our results show that it is also valid for the submerged MWPJ investigated in this study.…”
Section: The Effect Of N2 On Mwpj Characteristics and Plasma Dynamicssupporting
confidence: 72%
See 1 more Smart Citation
“…Figure 10c shows that, regardless of water conductivity, continuously increases from ~2700 K to ~3400 K as N2 content increases from 0 to 2.5%. Previous studies have shown that such increase in temperature is due to the excitation of N2 rotational levels, with contributions from other phenomena such as excitation of vibrational and electronic levels, ionization, and dissociation [25], [28], [29]. Although this explanation is very well accepted for gas-phase microwave plasmas, our results show that it is also valid for the submerged MWPJ investigated in this study.…”
Section: The Effect Of N2 On Mwpj Characteristics and Plasma Dynamicssupporting
confidence: 72%
“…Adding N2 to Ar significantly influences plasma properties, including electron density, electron temperature, and gas temperature [28], [29]. Recently, we have shown that the addition of 1-2% N2 to the Ar flow in MWPJ improves the efficiency of MB degradation [21].…”
Section: The Effect Of N2 On Mwpj Characteristics and Plasma Dynamicsmentioning
confidence: 99%
“…For a successful graphene synthesis, a delicate balance among all these intrinsically interconnected processes is needed. Such balance can be significantly altered by the presence of a reactive gas (e.g., O 2 or H 2 ), as it affects both plasma parameters [ 50 ] and chemical composition. [ 51 ] This can be either unintentional (impurities) or intentional (deliberate admixture).…”
Section: Resultsmentioning
confidence: 99%
“…The results clearly show a decrease in the width of Hα lines, thus, a decrease in electron density with increasing N 2 content (phenomena already reported) for both conditions of d . In fact, the addition of N 2 to Ar, even at very low percentages (<1%), is well known to induce a decrease in electron density due to power loss by molecular excitation/ionization phenomena that undermine the ionization of Ar and the production of electrons …”
Section: Resultsmentioning
confidence: 99%
“…The results clearly show a decrease in the width of Hα lines, thus, a decrease in electron density with increasing N 2 content (phenomena already reported [34,35] ) for both conditions of d. In fact, the addition of N 2 to Ar, even at very low percentages (<1%), is well known to induce a decrease in electron density due to power loss by molecular excitation/ ionization phenomena that undermine the ionization of Ar and the production of electrons. [36] Gas temperature measurements in plasmas are often obtained by emission spectroscopy from the population distribution in rotational levels of excited states of diatomic molecules (such as OH, NH, N 2 + , etc.). In plasma conditions very close to ours, OH (A-X) was found to be the best reliable probe to obtain a satisfactory estimation of the gas temperature, due to the highly favorable exchange energy of heavy particles and the internal rotational-vibrational states of this molecular species.…”
Section: Plasma Characteristics Under Various Conditionsmentioning
confidence: 99%